Management of Angsana Beach Tourist Attractions in Angsana District, Tanah Bumbu Regency - Defvy Ayuningtyas; Mutiani Mutiani; M. Ridha Ilhami; Raihanah Sari; Sigit Triyono (Universitas Lambung Mangkurat, 2025)
Referring to national regulations such as Government Regulation Number 50 of 2011 and Law Number 23 of 2014 concerning Regional Government, tourism management has become an important part of encouraging regional economic growth. The tourism management process is carried out by the local government together with the local community, which has an impact on economic, social, cultural, and environmental aspects. This study aims to identify the management of Angsana Beach tourist attractions in Angsana District, Tanah Bumbu Regency. The research method used is a qualitative approach by utilizing primary and secondary data, as well as analytical techniques including data reduction, data presentation, and validation through triangulation. The results of this study show that management is carried out synergistically by various parties, including the village government, Pokdarwis, Pokmaswas, the Sustainable Green community, and supported by the Tourism Office and the Environment Office. This management focuses on organizational and supervisory aspects, such as ticket sales, small and medium enterprises (SMEs), accommodation, and other tourism facilities. Human resource development is carried out through training and empowerment. Waste management still faces technical issues and a lack of awareness among visitors, while challenges such as extreme weather and an increase in the number of tourists during the holiday season are also affecting management. The positive results of this management include local economic growth, increased social and cultural interaction, and environmental conservation through zoning and embankment construction. These findings also contribute academically and practically, including as a reference source for social studies lessons at the junior high school level on economic potential and community empowerment.